Radiometric Analysis of Canal and Body of Lumbar Vertebrae among Population of Central Nepal - Mansur, Dil Islam; Karki, Subindra; Mehta, Dilip Kumar; Shrestha, Pragya; Maskey, Sunima; Shrestha, Sheprala (Journal of College of Medical Sciences-Nepal, 2020)
Background: Lumbar region is the most vulnerable area for the common symptom of backache. The lumbar part of spinal canal encloses the cauda equina. Narrowing of the canal can be either developmental or acquired. This leads to compression of the cauda equina and subsequently pain develops which may be further associated with neurological features. The aim of the present study was to measure the dimensions of lumbar vertebrae. Methods: The present study was a descriptive and cross-sectional type. It consisted of 266 images of computed tomography scan of individuals. The various dimensions of lumbar vertebral canal and body were measured in millimeter. The descriptive statistical analysis was done. Results: The mean of the transverse diameter of lumbar vertebral canal increased from L1 to L5 but the antero-posterior diameter decreased from L1 to L4 followed by increased at L5. It was also observed that both transverse and antero-posterior diameter of body progressively increased from L1 to L5 vertebrae. The canal-body ratio was inconsistent for lumbar vertebrae. There were significant differences in various dimensions of lumbar vertebrae between males and females. Conclusions: The anatomical knowledge of the dimensions of canal and body of lumbar vertebral may be helpful for the clinicians during radiological interpretations and surgical procedures of lumbar spine pathology. Keywords: back pain; lumbar vertebrae; stenosis.